A Conceptual Model on People Approach and Smart Manufacturing - Baizura Ramzi; Hartini Ahmad; Nazlina Zakaria (International Journal of Supply Chain Management, 2019)
The purpose of this study is to emphasize the important role of people approach in the revolution of smart manufacturing and industry 4.0. Two hundred years ago, industrial revolution in the West transformed or evolved from water-driven or water-driven mechanical production, and to date, we are in an era characterized by cyber-physical systems. This transformation or industrial revolution was driven by people who used creative minds to solve problems. Rapid development of technology has brought about many disruptive technologies such as big data, artificial intelligence and cloud computing. These technologies are penetrating almost in all industries include manufacturing industry. The fusion of these state-of-the-art technologies and manufacturing brings together the physical and virtual worlds through Cyber-Physical System (CPS), which marks the advent of the fourth stage of industrial production – Industry 4.0.